Persistence of cholinergic neurons in the basal nucleus in a brain with senile dementia of the Alzheimer's type demonstrated by immunohistochemical staining for choline acetyltransferase. - Pearson, R; Sofroniew, M; Cuello, A; Powell, T; Eckenstein, F; Esiri, M; Wilcock, G (1983)
Immunohistochemically identified cholinergic neurons in the basal nucleus of Meynert in a brain with SDAT have been compared with those in two age- and sex-matched normal brains. The numbers of such cells at carefully matched levels are not significantly lower, but the cells in SDAT are substantially smaller than in the normal basal nucleus. The persistence of shrunken cholinergic neurons in the basal nucleus in the diseased brain is similar to that seen in an experimental study of retrograde cellular degeneration in the nucleus following damage of the cortex.